Adipose-targeted overexpression of mitochondrial-targeted catalase does not improve cardio-metabolic parameters in mice with diet-induced obesity. (14th October 2021) - Croft, A J; Kelly, C; Chen, D; Murtha, L; Sugito, S; Boyle, A; Sverdlov, A L; Ngo, D T M
Abstract: Background: Obesity is associated with significant cardio-metabolic complications. Adipokines, and cytokines released from adipose tissue (AT) stimulate excessive mitochondrial production of reactive oxygen species (ROS). ROS-mediated oxidative modifications is associated with development of insulin resistance and impaired cardiac function. We hypothesised that adipose-targeted overexpression of mitochondrial-targeted catalase (AT-mCAT) could lead to improvement in diet-induced cardio-metabolic dysfunction. Methods/Results: mCAT (floxed) and AdipoQ-Cre mice were crossed to generate mice overexpressing catalase with a mitochondrial-targeting sequence predominantly in AT (AT-mCAT). Wild-type (WT) and AT-mCAT male mice were fed normal chow (NC) or high-fat/high-sucrose (HFHS) diet (36%fat/34%sucrose) for 4 months. At endpoint, echocardiography showed reduced cardiac output in all groups v WT NC (p<0.05); reduced IVSd in AT-mCAT NC and HFHS groups v WT NC (p<0.01); reduced left ventricular ejection fraction in AT-mCAT HFHS v WT NC (p<0.05) and no differences in fractional shortening or E/A ratio between groups. Glucose tolerance tests (2g/kg) showed impairment in WT HFHS and AT-mCAT HFHS v WT NC (p<0.01, p<0.05 respectively). Triglyceride levels were increased in WT HFHS and AT-mCAT HFHS v WT NC (p<0.05). Analysis of hypertrophic signalling in cardiac tissues by ELISA showed p-AKT/total Akt levels were decreased in AT-mCAT hearts regardless of diet (WT NC v AT-mCAT NC p<0.01; WT HFHS v AT-mCAT HFHS p<0.05). Conclusion: Our results confirm previous findings that diet-induced obesity is a systemic condition. Targeting adipose tissue with mitochondrial catalase may not be adequate to prevent development of cardio-metabolic dysfunction. More systemic approaches may be required to combat obesity-induced cardio-metabolic impairment. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Heart Foundation of Australia